In silico characterization of the interaction of AKR1B1 with the deacetylase activation domain (DAD) - Francisco J. Gómez-Zaldívar; Francisco J. Gómez-Zaldívar; Luis Córdova-Bahena; Luis Córdova-Bahena; Angel J. Ruiz-Moreno; Paolo Ceppi; Paolo Ceppi; Marco A. Velasco-Velázquez (Frontiers in Molecular Biosciences)
The aldo-keto reductase family 1 member B1 (AKR1B1) plays a key role in cancer progression by competing with histone deacetylase 3 to bind to the deacetylase activation domain (DAD) of the nuclear receptor corepressor SMRT. Previous studies showed that the L289A mutation in AKR1B1 disrupts its ability to form a dimer with DAD but further details of this interaction remain uncharacterized. This study aimed to model the DAD/AKR1B1 dimer by molecular docking and characterize the complex using molecular dynamics simulations. We identified a new model with increased structural stability for AKR1B1, reduced disruption of secondary structures of DAD, and lower ΔG than a previously reported one. In silico mutagenesis of AKR1B1 assessed the contributions from individual residues. We identified six hotspot residues that mediate the complex interface. Those residues are located in the α8 and H2 alpha helices of AKR1B1 and include the experimentally determined L289. These results propose new hypotheses regarding the interaction between DAD and AKR1B1, guiding future experimental approaches.